2018
DOI: 10.1097/jtn.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Catheter-Associated Urinary Tract Infections in a Trauma Population: A 5-S Bundle Preventive Approach

Abstract: Complications from catheter-associated urinary tract infections (CAUTIs) can cause morbidity and mortality. Our institution's Trauma Quality and Improvement Program analysis identified CAUTIs as an outlier complication in our trauma population. This study aimed to determine whether implemented measures would reduce CAUTI rates in trauma population. A 5-S CAUTI bundle was implemented. Its effects were measured on a prospectively collected dataset of adult trauma patients using our Trauma Registry during the 4-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…A recent systematic review and meta-analysis by Schreiber et al [28] reported that HAI reductions of 35-55% can be achieved with multifaceted interventions. In one study, the implementation of multiple measures for preventing CAUTI ("5-S CAUTI bundle", an approach that included education, catheter stabilization, correct positioning of the collection bag and daily evaluation) resulted in a statistically significant 80% reduction in CAUTI rate [29]. This is in the same range as the reduction achieved in the present study with the NMA-coated BIP Foley Catheter (69%).…”
Section: Discussionsupporting
confidence: 65%
“…A recent systematic review and meta-analysis by Schreiber et al [28] reported that HAI reductions of 35-55% can be achieved with multifaceted interventions. In one study, the implementation of multiple measures for preventing CAUTI ("5-S CAUTI bundle", an approach that included education, catheter stabilization, correct positioning of the collection bag and daily evaluation) resulted in a statistically significant 80% reduction in CAUTI rate [29]. This is in the same range as the reduction achieved in the present study with the NMA-coated BIP Foley Catheter (69%).…”
Section: Discussionsupporting
confidence: 65%
“…To our knowledge, this is the first study to evaluate clinical outcomes in a national cohort of trauma patients with CAUTI since the CDC CAUTI surveillance definition change in January 2015 [6]. Several other studies have evaluated CAUTIs among trauma patients [8,9,[15][16][17][18]; however, only one study employed the current CDC surveillance definition for CAUTI [9]. The incidence of CAUTI observed in our study was 0.7%, which is similar to the rate of 0.3%-1.3% observed by Elkbuli et al [9] over a previous 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, CAUTIs pose a significant burden on the healthcare system, and considerable effort has been put forth to reduce the CAUTI rates. Multiple studies have focused on reducing the rate of CAUTIs by decreasing catheter use, employing ''care bundles,'' and changing culturing practices [8][9][10][11][12]. These efforts have resulted in decreased catheter days, but the overall rate of CAUTI has remained similar [2,8,13,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic prophylaxis can reduce the incidence of CAUTI’s throughout the duration of an indwelling catheter [21], but further precautions are necessary. Nursing education for proper bladder bag placement and twice-daily perineal care reduces CAUTI’s as much as 70% in trauma patients [22]. On discharge, patients are instructed to continue these measures until one-week outpatient follow up.…”
Section: Discussionmentioning
confidence: 99%